The Fukushima effect at home: The changing role of domestic actors in Japanese energy policy. (8th June 2020) - Fraser, Timothy; Aldrich, Daniel P.
Abstract: This paper reviews the changing role of domestic political institutions, including local governments and courts, in Japan's energy policy over the 8 years since the Fukushima disaster, focusing on the nuclear and renewable power industries. We explain how a variety of hidden subsidies created financial dependency in communities hosting nuclear power plants and led to local officials hoping to restart nuclear power plants after the meltdowns despite wide‐scale opposition. Later, the introduction of a feed‐in tariff (FiT) brought a wider range of towns into the field of renewable energy, but vulnerable towns with weaker social networks continue to bear a large share of Japan's energy infrastructure. Courts, prefectures, and local firms have become intervening agents in the renewable energy market, but utilities have pushed back, encouraging the state to overturn the FiT and create auctions for renewable power contracts instead. With subnational governments and courts more powerful in energy policy since the meltdowns, and a variety of new actors involved in renewable energy, post‐Fukushima energy policy has become more democratized. This article is categorized under: The Carbon Economy and Climate Mitigation > Decarbonizing Energy and/or Reducing Demand Abstract : The Awaji‐Kifune Mega‐Solar Power Plant (34.7 MW) uses mountainside land in Hyogo Prefecture that was harvested to build the Kansai International Airport. Team‐ups between regional companies, landowners, and local governments are shaping Japanese energy policy from the bottom‐up. (Photo by authors).